Tamsulosin is beneficial for distal, larger stone (5–10 mm) passage. Issue 2 (February 2018) - Hughes, Pamela R.
Abstract : N/A: Wang RC, Smith‐Bindman R, Whitaker E, Neilson J, Allen IE, Stoller ML, et al. Effect of tamsulosin on stone passage for ureteral stones: a systematic review and meta‐analysis. Ann Emerg Med . 2017; 69(3):353–361.e3.